Genomewide association study of peanut allergy reproduces association with amino acid polymorphisms in HLA‐DRB1. Issue 2 (11th January 2017) - Martino, D. J.; Ashley, S.; Koplin, J.; Ellis, J.; Saffery, R.; Dharmage, S. C.; Gurrin, L.; Matheson, M. C.; Kalb, B.; Marenholz, I.; Beyer, K.; Lee, Y.‐A.; et al.
Summary: Background: Genetic variants for IgE‐mediated peanut allergy are yet to be fully characterized and to date only one genomewide association study (GWAS) has been published. Objective: To identify genetic variants associated with challenge‐proven peanut allergy. Methods: We carried out a GWAS comparing 73 infants with challenge‐proven IgE‐mediated peanut allergy against 148 non‐allergic infants (all 1 year old). We tested a total of 3.8 million single nucleotide polymorphisms, as well as imputed HLA alleles and amino acids. Replication was assessed by de novo genotyping in a panel of additional 117 cases and 380 controls, and in silico testing in two independent GWAS cohorts. Results: We identified 21 independent associations at P ≤ 5 × 10 −5 but were unable to replicate these. The most significant HLA association was the previously reported amino acid variant located at position 71, within the peptide‐binding groove of HLA‐DRB1 ( P = 2 × 10 −4 ). Our study therefore reproduced previous findings for the association between peanut allergy and HLA‐DRB1 in this Australian population. Conclusions and Clinical Relevance: Genetic determinants for challenge‐proven peanut allergy include alleles at the HLA‐DRB1 locus.